Physical responses by cerebral palsy footballers in matches played at sea level and moderate altitude - Henríquez, M.; Castillo, D.; Yanci, J.; Iturricastillo, A.; Reina, R. (Research in Sports Medicine, 2023)
The main objective of this study was to compare the physical response of para-footballers with cerebral palsy (CP) in official international football matches played at moderate altitude and sea level locations. Eighty-seven international CP footballers participated in this study. We divided participants according to the place of the international competition [sea level group (SLG) and moderate altitude group (MAG)], sport classes (i.e., FT1, FT2, and FT3), and match playing time (i.e., <20 min, 20-40 min, and >40 min). We recorded the physical response using global position system devices during matches. This study showed that MAG described a lower physical response than SLG on total distance, distance covered at different intensities, and the number of accelerations and decelerations. FT2 and FT3 presented a similar pattern, where we found significant differences for total distance, distance covered at lower and high intensities and moderate accelerations, and decelerations. Considering the playing time during altitude matches, the 20-40 min and >40 min groups obtained more marked differences in the physical response variables. Para-footballers with CP who competed under altitude conditions showed a lower physical response during football matches, suggesting the implementation of specific preparation and training strategies to face the demanding environmental conditions.